Fabrication, application, optimization and working mechanism of Fe2O3 and its composites for contaminants elimination from wastewater. (January 2021) - Tao, Qingqing; Bi, Jingtao; Huang, Xin; Wei, Rongli; Wang, Ting; Zhou, Yanan; Hao, Hongxun
Abstract: Fe2 O3 and its composites have been extensively investigated and employed for the remediation of contaminated water with the characteristics of low cost, outstanding chemical stability, high efficiency of visible light utilization, excellent magnetic ability and abundant active sites for adsorption and degradation. In this review, the potentials of Fe2 O3 in water remediation were discussed and summarized in detail. Firstly, various synthesis methods of Fe2 O3 and its composites were reviewed and compared. Based on the structures and characteristics of the obtained materials, their applications and related mechanisms in pollutants removal were surveyed and discussed. Furthermore, several strategies for optimizing the remediation processes, including dispersion, immobilization, nano/micromotor construction and simultaneous decontamination, were also highlighted and discussed. Finally, recommendations for further work in the development of novel Fe2 O3 -related materials and its practical applications were proposed. Graphical abstract: Image 1 Highlights: Synthesis methods of Fe2 O3 materials are outlined and compared. Applications and optimization strategies are summarized and discussed. Mechanisms responsible for removing various pollutants are concluded.